1978
DOI: 10.1136/sti.54.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes in syphilitic nephropathy. A case report.

Abstract: SUMMARY A case of transient nephrotic syndrome caused by secondary syphilis is described. A renal biopsy was performed revealing subepithelial hump-like electron-dense deposits and fusion of epithelial foot-processes. Complement Clq-binding-activity and anticomplementarity were demonstrated in the blood, indicating the presence of circulating immune complexes. This strongly suggests that circulating immune complexes are significant in the immunopathogenesis of syphilitic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…2 Using a radioimmunoassay, S0lling and his co-workers3 4 also demonstrated circulating ICs in early syphilis and in a case of syphilitic nephropathy. Gamble 7 The principles of the method are precipitation of the ICs in barbital-HCI buffer (pH 8 4) containing 3-5% PEG, sedimentation of the complexes by centrifugation at 12 000 x g, dissolution of the precipitates in Biurets reagent, and measurement of the optical density at 550 nm (protein determination).…”
Section: Introductionmentioning
confidence: 99%
“…2 Using a radioimmunoassay, S0lling and his co-workers3 4 also demonstrated circulating ICs in early syphilis and in a case of syphilitic nephropathy. Gamble 7 The principles of the method are precipitation of the ICs in barbital-HCI buffer (pH 8 4) containing 3-5% PEG, sedimentation of the complexes by centrifugation at 12 000 x g, dissolution of the precipitates in Biurets reagent, and measurement of the optical density at 550 nm (protein determination).…”
Section: Introductionmentioning
confidence: 99%
“…Jorizzo et al [161, found immune complexes in the damaged vessel wall and in the skin, which suggested that CIC could be translocated. Deposits of immune complexes were also found on the glomerular basement membrane in syphilitic nephropathy [17] and it was suggested that they take part in the pathogenesis of syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…Membranous glomerulonephritis (MGN), as seen in this case, is the most commonly observed histopathological lesion, and is thought to be mediated by immune complex deposition within the capillary walls [3][4][5][6][7][8][9]. Renal function is normal in most cases, but this case is reported to involve acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 99%